Investigation On The Crystal Structure, Third-Order Nonlinear Optical And Thermal Studies Of 4-Nitroanilinium 5-Sulfosalicylic Acid Monohydrate Single Crystal - P.K., Siva Kumar; M, Krishna Kumar; R, Mohan Kumar; S.R., Kanagadurai (Photonics Letters of Poland, 2015)
<!-- saved from url=(0022)http://internet.e-mail --> 4-Nitroanilinium 5-Sulfosalicylic acid monohydrate (4NASA) was synthesized and single crystal was grown from ethanol: water mixed solvent. The crystal system of 4NASA was determined from the single crystal X-ray diffraction study. Absorption range of 4NASA compound was analyzed from the UV-visible absorption spectral studies. The nonlinear refractive index, nonlinear absorption coefficient and third-order nonlinear optical susceptibility of 4NASA crystal were calculated by Z-scan technique. Thermal behavior of the grown crystal was elucidated by using TG-DTA analysis. Full Text: PDF References D.F. Eaton, "Nonlinear Optical Materials", Science 253, 281 (1991). CrossRef R.L. Sutherland, Handbook of Nonlinear Optics (Marcel Dekker Inc, New York 2003). CrossRef J.G. Breitzer, D.D. Dlott, L.K. Iwaki, S.M. Kirkpatrick, T.B. Rauchfuss, "Third-Order Nonlinear Optical Properties of Sulfur-Rich Compounds", J. Phys. Chem. A 103, 6930 (1999). CrossRef P.N. Prasad, D.J. Williams, Introduction to Nonlinear Optical Effects in Organic Molecules and Polymers (Wiley, New York 1991). P.K. Sivakumar, M. Krishna Kumar, G. Chakkaravarthi, R. Mohan Kumar, R. Kanagadurai, "4-Nitroanilinium 3-carboxy-4-hydroxybenzenesulfonate monohydrate", Acta Cryst. E 69, 1609 (2013). CrossRef S. Anandhi, T.S. Shyju, T.P. Srinivasan, R. Gopalakrishnan, "Investigation on growth and characterization of imidazolium picrate: An organic salt", J. Cryst. Growth 335, 75 (2011). CrossRef A. Chandramohan, R. Bharathikannan, M.A. Kandhaswamy, J. Chandrasekaran, R. Renganathan, V. Kandavelu, "Synthesis, spectral, thermal and NLO properties of N,N -Dimethyl anilinium picrate", Cryst. Res. Technol. 43, 173 (2008). CrossRef W. Lei, X. L.Yan, X. RuiFeng, L. XiFeng, C. Raisin, T. XuTang, "Hydrogen-bonding directed cocrystallization of flexible piperazine with hydroxybenzoic acid derivatives: Structural diversity and synthon prediction", Sci. China Chem. 55, 1138 (2012). CrossRef F. Khammar, A.P. Kerasidou, K. Iliopoulos, P. Savel, H. Akdas- Kilig Y. Hamaizi, J.-L. Fillaut, B. Sahraoui, "Effect of metal complexation on the nonlinear optical response of a conjugated ligand", J. Opt. Soc. Am. B. 07, 1555 (2014). CrossRef F.L.S. Cuppo, A.M.F. Neto, S.L. Gomeze, P.P. Muhoray, "Thermal-lens model compared with the Sheik-Bahae formalism in interpreting Z-scan experiments on lyotropic liquid crystals", J. Opt. Soc. Am. B 19, 1342 (2002). CrossRef M. Krishna Kumar, S. Sudhahar, A. Silambarasan, B.M. Sornamurthy, R. Mohan Kumar, "Crystal growth, structural, linear and nonlinear optical studies of 4-methyl-4?-N?-methylstilbazolium tosylate single crystals", Optik 125,751 (2014). CrossRef M. Sheik-Bahae, A.A. Said, T.H. Wei, D.J. Hagan, E.W. Van Stryland, "Sensitive measurement of optical nonlinearities using a single beam", J. Quantum Electron. 26,760 (1990). CrossRef K. Iliopoulos, I. Guezguez, A.P. Kerasidou, A-El. Ghayoury, D. Branzea, G. Nita, N. Avarvari, H. Belmabrouk, S. Couris, B. Sahraoui, "Effect of metal cation complexation on the nonlinear optical response of an electroactive bisiminopyridine ligand", Dyes and Pigments 101, 229 (2014). CrossRef T.C. Sabari Girisun, S. Dhanuskodi, D. Mangalaraj, J. Phillip, "Synthesis, growth and characterization of bisthiourea zinc bromide for optical limiting applications", Current. Appl. Phys. 11, 838 (2011). CrossRef A.I. Vodchits, V.P. Kozich, V.A. Orlovich, P.A. Apanasevich, "Z-Scan studies of KYW, KYbW, KGW, and Ba(NO3)2 crystals", Opt. Commun. 263, 304 (2006). CrossRef H.P. Li, C.H. Kam, Y.L. Lam, W. Ji, "Femtosecond Z-scan measurements of nonlinear refraction in nonlinear optical crystals", Opt. Mater. 15, 237 (2001). CrossRef